The Holocausts - Morawiec, Arkadiusz (Poznańskie Studia Slawistyczne, 2017)
The article examines genocide as a category that has been used and abused in various, especially historical, political, and ideological, discourses. It considers whether the extermination of Jews (the Holocaust) should be studied in the context of other mass crimes. I investigate various sources of twentieth-century organized violence and their literary representations. I also discuss the works of Polish literature (by Nałkowska, Gębarski, Woroszylski, and Margolis), which depict twentieth- -century acts of genocide (the extermination of Jews and Armenians, in particular) in the context of other mass crimes.